2020
DOI: 10.2989/1814232x.2020.1776391
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of nutrients and primary productivity in the Rufiji Delta mangroves, Tanzania

Abstract: Determinations of spatial and temporal variations in organic matter and nutrient dynamics in water and sediments are crucial for understanding changes in aquatic bodies. In this study, we (i) determine the spatial dynamics of dissolved inorganic nutrients, during the transition from the dry to the rainy season, and (ii) provide future productivity predictions for the Rufiji Delta mangroves, Tanzania, based on the input of various nutrients. Water samples were collected from six locations, three times per year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…Among them, A. officinalis, R. mucronata, and X. granatum were promising nutritional and antioxidant materials sources.This study's nutritional values were almost similar values with those previous studies [19]- [21], even much higher value than reported in Rawn Park [12]. Mangroves are known as source of some secondary metabolites and utilized for antibacterial and antifungal [22], antifeedant [23], and property [24].…”
Section: Element Analysissupporting
confidence: 85%
“…Among them, A. officinalis, R. mucronata, and X. granatum were promising nutritional and antioxidant materials sources.This study's nutritional values were almost similar values with those previous studies [19]- [21], even much higher value than reported in Rawn Park [12]. Mangroves are known as source of some secondary metabolites and utilized for antibacterial and antifungal [22], antifeedant [23], and property [24].…”
Section: Element Analysissupporting
confidence: 85%
“…The present study was conducted to determine the effects of the combinations of three different temperature levels (27 °C, 31 °C and 35 °C) and three salinity levels (30 ppt, 35 ppt and 40 ppt) on incubation time, hatching success, larvae and postlarvae survival of Penaeus monodon. The highest temperature and salinity chosen for this study were relatively higher than those found in the Rufiji Delta (8.2-31.2 °C and 2-32 ppt) (Minu et al 2020), where the P. monodon broodstock were taken. The results of the study indicate reduced incubation time for P. monodon eggs at high temperature and high salinity combinations which could be linked to increased egg development rate due to increased metabolic rates (Bett and Vinatea 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The average temperature and salinity in the Rufiji Delta where the broodstock (spawners) were collected are 28.2-31.2 °C and 2-32 ppt, respectively (Minu et al 2020). The experiments were conducted at three different temperature groups of 27 °C, 31 °C and 35 °C.…”
Section: Temperature-salinity Experimentsmentioning
confidence: 99%
“…The value of DO in all locations did not meet the Indonesian government standard, i.e.> 5 mg/L. Some human activities can increase the level of pollutants and sediment in the water, further reducing the DO concentration in the water for the degradation process [30] [31].…”
Section: Water and Plant Diversity Quality In The Riparian Zone Of Ta...mentioning
confidence: 95%